Review paperThe role of fungi in allergic diseases - Żukiewicz-Sobczak, Wioletta A. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Allergic diseases such as allergic rhinitis, pharyngitis, laryngitis, asthma, airborne dermatitis, or allergic conjunctivitis, can be caused or aggravated by components of bioaerosol from natural environment or from indoor environment in enclosed spaces, workplaces and homes. The main components of bioaerosol are fungi and their metabolites, which are common in the environment.